Progress in total synthesis of subincanadine alkaloids and their congeners - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
A concise account of isolation, characterization, bioactivity, plausible biogenetic pathways, and most importantly, total synthesis of structurally fascinating and biologically imperious indole-based subincanadine alkaloids and their biogenetic congeners are described in the present review with special emphasis on total synthesis and therein an involved set of key reactions.